Genetic architecture of body weight, carcass, and internal organs traits of Ghanaian local chickens - Kanlisi, Roland A.; Amuzu-Aweh, Esinam N.; Naazie, Augustine; Otsyina, Hope R.; Kelly, Terra R.; Gallardo, Rodrigo A.; Lamont, Susan J.; Zhou, Huaijun; Dekkers, Jack; Kayang, Boniface B. (Frontiers in Genetics, 2024)
Information on the genetic architecture of the production traits of indigenous African chicken is limited. We performed a genome-wide association study using imputed Affymetrix Axiom® 600K SNP-chip genotypes on 1,113 chickens from three agroecological zones of Ghana. After quality control. a total of 382,240 SNPs remained. Variance components and heritabilities for some growth, carcass and internal organ traits were estimated. The genetic and phenotypic correlations among these traits were also estimated. The estimated heritabilities of body weight at week 22 (BW22), average daily gain (ADG), dressed weight, breast weight, thigh weight, wing weight, drumstick weight, and neck weight were high and ranged from 0.50 to 0.69. Estimates of heritabilities for head weight, shank weight, and gizzard weight were moderate (0.31-0.35) while those of liver weight, back weight, dressing percentage, and heart weight were low (0.13-0.21). The estimated heritabilities of dressed weight, breast weight, wing weight, drumstick weight, neck weight, shank weight, and gizzard weight, corrected for BW22, were moderate (0.29-0.38), while the remaining traits had low heritability estimates (0.13-0.21). A total of 58 1-Mb SNP windows on chromosomes 1, 2, 4, 5, 6, 7, 8, 9, 13, 18, and 33 each explained more than 1% of the genetic variance for at least one of these traits. These genomic regions contained many genes previously reported to have effects on growth, carcass, and internal organ traits of chickens, including EMX2, CALCUL1, ACVR1B, CACNB1, RB1, MLNR, FOXO1, NCARPG, LCORL, LAP3, LDB2, KPNA3, and CAB39L. The moderate to high heritability estimates and high positive genetic correlations suggest that BW22, ADG, dressed weight, breast weight, thigh weight, wing weight, drumstick weight, and neck weight could be improved through selective breeding.